PEMBERIAN BERBAGAI JENIS BIOCHAR TERHADAP PERTUMBUHAN VEGETATIVE TANAMAN CABAI RAWIT VARIETAS HIYUNG (capsicum frutescens L.) - Rory Mahendra; Antar Sofyan; Noor Laili Aziza (Agroekotek View, 2021)
Chili pepper has high economic value so that it gets priority to be cultivated. The famous type of chili pepper in South Kalimantan is hiyung variaty of chili pepper which have very high spiciness and long shelf life. One of material that is able to increase plant growth is biochar. Biochar or better known as charcoal is a solid material formed from carbonization of biomass. Biochar can be added to the soil in order to improve soil function and reduce emissions from biomass that naturally breaks down into greenhouse gases. Biochar also has the function of binding carbon quite large. The purpose of this research was to determine the effect of biochar administration on the vegetative growth of hiyung variety of chili peper (C. frutescens L.) and to find out the best types of biochar for vegetative growth of chili pepper (C. frutescens L.). The research began in October 2019 and was completed in January 2020 at Bina Murni street, North Loktabat Village, North Banjarbaru District, Banjarbaru City, South Kalimantan. This study used one factor a completely randomized design (RCBD), namely s1 (biochar rice husk 80 g.polybag-1 ≈20 t.ha-1), s2 (biochar sawdust 80 g.polybag-1 ≈ 20 t.ha-1) and s3 (biochar coconut shell 80 g.polybag-1 ≈ 20 t.ha-1). Aplication of various kinds of biochar did not significantly affect the vegetative growth of hiyung varuaty of chili pepper (C. frutescens L.). In this study, the best type of biochar was not found for vegetative growth of hiyung chili plants.